Development of Assessment Tools for Understanding Submicroscopic Representations in Acid-Base Material - Ardhana, Ivan Ashif; Hidayah, Rahayu Nur; ‘Aisy, Syandifa Rohadlotul; Ijtihadah, Mustabsyirotul (Universitas Pendidikan Mandalika, 2025)
Acid-base material should ideally be evaluated holistically through the triplet of macroscopic, submicroscopic, and symbolic representations. However, the assessments conducted so far have primarily not evaluated the ability to understand submicroscopic representations and still focus on macroscopic and symbolic representations. Therefore, this research aims to develop an instrument for assessing submicroscopic understanding of acid-base material and analyze its feasibility. The research method used is the 4D model development, carried out up to the develop stage. The results of the content validation by expert validators yielded an average score of 91.2%, which falls into the very valid category. The empirical test results on 116 chemistry teachers and prospective chemistry teachers showed that all items on the instrument were valid with a reliability of 0.60, which falls into the reliable category. Moreover, the instrument has varying levels of difficulty index and discrimination power. The test items' character in the instrument assesses understanding of submicroscopic representations of acid-base concepts such as solution properties, acid strength, acid constant, pH, and degree of dissociation. The recommendation for further research is the need to develop and apply submicroscopic understanding questions in other chemistry topics as a reinforcement in the assessment and evaluation process of chemistry learning.